PENGARUH KEMAMPUAN DAN MOTIVASI KERJA TERHADAP PEGAWAI NEGERI SIPIL DI BALAI DIKLAT KEAGAMAAN SEMARANG - Ismail Niko Handoyo; Tri Yuniningsih; Mochamad Mustam (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
As the state of apparatus an employee should have an attitude and behavior which characterized the devotion, and should have high work discipline so that they can give a good service to the society. It can assumed that most of State Employee or Pegawai Negeri Sipil (PNS) in Balai Diklat Keagamaan Semarang or Religion Affairs Training Center Semarang has low quality performance, as we can see from the input performance, system of performance, quality of service for participants and widyaiswara. The research is used explanatory research. Methods of collecting data are observation, questionnaire, interview, and review of literature that has been analyzed quantitatively. To examine the hypothesis is used kendall rank coefficient-correlation, kongkordasi kendall coefficient, F test (simultaneous test), and to find out the relation between variables is used determined coefficient analysis which helped by SPSS program. It found significant relation between capability (X1) with employee performance (Y) and motivation (X2) with employee performance (Y) by using rank kendall correlation. But, there are not significant relation between capability (X1), motivation (X2), and employee performance (Y). With F test technique there are significant relations between capability (X1), motivation (X2), and employee performance (Y). The influence of employee ability (X1) to employee performance (Y) is 43,3%, the influence of motivation (X2) to employee performance is 25,5%, influence of ability (X1) and motivation (X2) to employee performance is 55,9% and the rest 44,1% are other factors which has influence with employee performance such as discipline, appreciation, and type leadership. The result showed that the influence of high ability (X1) and motivation of employee can minimize fault so that employee’s performance can be increased and they can do better in any aspects. The author provides recommendations of ability (X1) through training, softskill training, and technical guidance, whereas recommendations of motivation (X2) through giving a compliment, appraisement, and additional intensive.